Pre-competition anxiety and self-confidence in collegiate track and field athletes: a comparison between African American and non-Hispanic Caucasian men and women - Anagnostopoulos, V.; Carter, M. M.; Weissbrod, C. (The Sport Journal, 2015)
This study examined ethnic differences in the intensity and direction of pre-competition cognitive and somatic anxiety and self-confidence among Division I collegiate track and field men and women athletes. At a regular season track meet participants from seven Division I schools were approached and agreed to complete survey questions addressing competitive anxiety and win orientation. Study measures within three days of the event. Results were first analyzed by gender. It was found that the only difference between African American men and non-Hispanic Caucasian men athletes was that African American men reported lower cognitive direction scores than non-Hispanic Caucasian men. Among women, results indicated that African American women athletes reported less cognitive anxiety intensity and higher self-confidence than non-Hispanic Caucasian women. Interestingly, results also indicated few differences between African American women athletes as compared to either group of men athletes. Cultural factors are discussed that explain why African American women athletes are different from other groups.